Optimasi Ketebalan Dinding Sel Dan Material Inti Sandwich Honeycomb Board Pada Pintu KRL Commuter Line Menggunakan Metode Elemen Hingga - Susanto, Agus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2025)
One of the important mechanical parts of the Commuter Line electric train (KRL) that must be considered in designing is the door. This is because it experiences lateral loads when the train is operating. KRL doors consist of a frame, outer layer as skin, glass, and filling material which is usually filled with a honeycomb sandwich structure. As a door filling material, the honeycomb sandwich board has the largest volume compared to other door components, causing it to be heavier. This study focuses on optimizing the thickness of the cell wall to reduce the weight of the honeycomb sandwich board while still maintaining its mechanical strength and safety. Optimization was carried out using the finite element method (MEH) by comparing 6 door models. The thickness of the cell wall was varied between 0.0508; 0.0635; and 0.0762 mm with polypropylene and aluminum alloy 5052-H34 used as the material. Korean Railway Standards (KRS CB 0001-10 (R)) on “Entrance Door for Electric Car” and the Law of Indonesia Transportation Minister, PM. 175, 2015 on “Standard Technical Specification for Self-Propelled Normal Speed Trains” was adopted in the numerical calculation (MEH). The results showed that the door of the Commuter Line model 1 showed a weight reduction of up to 1.95% from the existing model, with a total weight of 31,816 kg. With a load of 588.4 N, the door design experienced a stress of 21 MPa and a deflection of 1.33 mm (maximum). When the load was 980.67 N, the door design experienced a stress of 35 MPa and a maximum deflection of 2.2 mm. With both loads, the proposed design still met the regulations of the Minister of Transportation.